IDENTIFIKASI POTENSI PENYEBAR BENIH TUMBUHAN PADA HUTAN RAWA GAMBUT DALAM RANGKA REGENERASI ALAMI DAN RESTORASI LAHAN GAMBUT PASCA KEBAKARAN - Saleh, Zuhratus; Tamin, Rike Puspitasari; Ulfa, Maria (Fakultas Kehutanan Universitas Lancang Kuning, 2021)
Tahura Orang Kayo Hitam is one of the locations that was severely damaged due to forest fires that occurred in the peat area of Jambi Province. Natural regeneration is a possible option in restoration activities and requires the presence of a mother tree and seed dispersing agents . This study aims to identify seed dispersing agents in the Orang Kayo HitamTahura and has been carried out for 3 months from June to August 2020. These tree species were obtained by a sampling method with a plot size of 20x20 m determined by a 500 m long transect from outside the forest to inside the forest. All trees with a diameter above 10 cm were measured and their species identified. Seed dispersing agents were identified by literature study, photo analysis and discussion with locals. The results of field data indicated that the species found in the study area were spread by wind and wildlife. From the 32 tree species were found, 10 species (32%) were spread by the wind and 22 species (68%) were spread by wild animals. The preliminary conclusion of this study is that wind and wildlife are very important in the distribution of tree seeds in burned areas.